Protein Targeting Into the Thylakoid Membrane Through Different Pathways - Zhu, Dan; Xiong, Haibo; Wu, Jianghao; Zheng, Canhui; Lu, Dandan; Zhang, Lixin; Xu, Xiumei (Frontiers in Physiology, 2022)
In higher plants, chloroplasts are essential semi-autonomous organelles with complex compartments. As part of these sub-organellar compartments, the sheet-like thylakoid membranes contain abundant light-absorbing chlorophylls bound to the light-harvesting proteins and to some of the reaction center proteins. About half of the thylakoid membrane proteins are encoded by nuclear genes and synthesized in the cytosol as precursors before being imported into the chloroplast. After translocation across the chloroplast envelope by the Toc/Tic system, these proteins are subsequently inserted into or translocated across the thylakoid membranes through distinct pathways. The other half of thylakoid proteins are encoded by the chloroplast genome, synthesized in the stroma and integrated into the thylakoid through a cotranslational process. Much progress has been made in identification and functional characterization of new factors involved in protein targeting into the thylakoids, and new insights into this process have been gained. In this review, we introduce the distinct transport systems mediating the translocation of substrate proteins from chloroplast stroma to the thylakoid membrane, and present the recent advances in the identification of novel components mediating these pathways. Finally, we raise some unanswered questions involved in the targeting of chloroplast proteins into the thylakoid membrane, along with perspectives for future research. Keywords: chloroplast protein import, cpSRP pathway, cpGET pathway, spontaneous pathway, cotranslational protein transport